PRESCRIBING PATTERNS OF CEPHALOSPORIN IN CHILDREN FOLLOWING IMPLEMENTATION OF ANTIBIOTIC STEWARDSHIP PROGRAM IN A TERTIARY CARE HOSPITAL AT WESTERN INDIA - JOSHI, ANURADHA; KHUMBANI, URVI; GANJIWALE, JAISHREE; GANGULY, BARNA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to study the prescribing patterns of cephalosporins in children following the implementation of Antibiotic Stewardship Program (ASP) in a tertiary care hospital at western India. Methods: This was an observational study of records using data of pre- and post-implementation of ASP. Data were collected from case files of children admitted to pediatric wards in the years 2012 and 2014, respectively. Data were analyzed to find the prescribing pattern of cephalosporin and its appropriateness in relation to ASP program guidelines. Results: Three hundred case files were collected and analyzed (n=150 each from the year 2012 and 2014). The mean age of patients in both years was 6.21 years±5.63 (the year 2012) and 5.88 years±5.88 in (the year 2014). Majority of children, that is, 47.3% were suffering from infectious diseases in the year 2012 while in the year 2014, 38.7% suffered from infectious diseases. Post-implementation of ASP, there was an improvement in the appropriateness of cephalosporin prescribing in terms of prophylactic and empirical treatments. Switch over of parenteral cephalosporins to oral was observed in 54.0% patients in 2012, while in 2014, it was seen in 51.3% of patients. There was a 4.6% rise in prescriptions containing 1st generation cephalosporins. Overall there was a significant impact of ASP in terms of appropriate cephalosporin prescribing (p=0.039). Conclusion: Implementation of ASP and its adherence by pediatricians can improve antibiotic prescribing in children.